Desain Komponen Tambahan Pada Sepeda Untuk Frame Tenda Menggunakan Model Kano - Sari, Galuh Masita; Purnomo, Hari (Jurnal Ilmiah Teknik Industri, 2017)
The users of the bike is currently doing a lot of camping in the open sky. Security becomes one of the problems when in nature. Camping cyclists often feel a sense of worry when leaving the bike. Based on these needs, it is necessary additional design part on the bike that made the frame set up the tent. The method used in the design is the canoe method. This method is used to determine the desires of bicycle users based on the level of customer satisfaction to the product of tents and bicycle merging. The results of the study were 13 attributes included in the servqual dimension. Grouping attributes based on canoe categories are 6 attributes including attractive category, 2 must be attributes, 4 one-dimensional attributes, and 1 indifferent attribute. The size of the tents that are made has a length of 200 cm, width 240 cm and height 160 cm.